Effects of repetitive transcranial magnetic stimulation on prefrontal cortical activation in children with attention deficit hyperactivity disorder: a functional near-infrared spectroscopy study - Jing Wang; Zhuo Zou; Haoyu Huang; Yangping Zhang; Xuemei He; Hang Su; Wenjuan Wang; Yingjuan Chen; Yun Liu (Frontiers in Neurology, 2024)
BackgroundAttention deficit hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder characterized by inattention, impulsivity, and hyperactivity. With the continuous development of neuromodulation technology, Repetitive Transcranial Magnetic Stimulation (rTMS) has emerged as a potential non-invasive treatment for ADHD. However, there is a lack of research on the mechanism of rTMS for ADHD. Functional near infrared spectroscopy (fNIRS) is an optical imaging technique that reflects the brain function by measuring changes in blood oxygen concentration in brain tissue. Consequently, this research utilized fNIRS to examine the impact of rTMS on the core symptoms and prefrontal cortex activation in children with ADHD, which provides a reference for the clinical application of rTMS in the treatment of ADHD.MethodsForty children with ADHD were chosen as research subjects and randomly assigned to two groups: a treatment group (20 subjects) and a control group (20 subjects). The control group received non-pharmacological interventions, whereas the treatment group was administered rTMS in conjunction with non-pharmacological interventions. Clinical symptom improvement was evaluated using SNAP-IV scale scores both before and after treatment. Additionally, fNIRS was utilized to monitor alterations in the relative concentrations of oxyhemoglobin (HbO2) and deoxyhemoglobin (HbR) in the prefrontal cortex during resting state and during the Go/no-go task state, both pre- and post-treatment.ResultsIn conclusion, the study comprised 17 participants in the treatment group and 18 in the control group. Initially, the SNAP-scale scores were comparable between the groups, with no significant differences observed (p > 0.05). Post-treatment, a notable reduction in SNAP-scale scores was evident (p < 0.05), with the treatment group exhibiting a more pronounced decrease (p < 0.05). Following the intervention, both groups demonstrated enhanced Resting-state functional connectivity (RSFC) in the prefrontal cortex, as indicated by a significant increase compared to pre-treatment levels (p < 0.05). Specifically, the treatment group showed superior RSFC in the left dorsolateral prefrontal cortex, right dorsolateral prefrontal cortex, left medial prefrontal cortex, and right medial prefrontal cortex compared to the control group (p < 0.05). However, no significant differences were noted in RSFC of the left and right temporal lobes between the two groups (p > 0.05). In the Go/no-go task, the treatment group recorded higher mean HbO2 concentrations in the aforementioned prefrontal cortical regions compared to the control group (p < 0.05). Conversely, no statistically significant disparities were observed in the left and right temporal lobes of both groups.ConclusionrTMS shows promise as a treatment for ADHD by modulating prefrontal cortical activation. fNIRS provides a valuable method for assessing these effects, offering insights into the neurobiological mechanisms underlying rTMS therapy.